2020
DOI: 10.3389/fpsyt.2020.00522
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Whole-Body Cryotherapy as Add-on Therapy to Pharmacological Treatment of Depression—A Randomized Controlled Trial

Abstract: Introduction: Accumulating evidence indicates the effectiveness of cryogenic temperature interventions in rheumatoid arthritis, ankylosing spondylitis, fibromyalgia, multiple sclerosis, and chronic low back pain. The application of whole-body cryotherapy (WBC) in psychiatric aspects of medicine was also noted. Nevertheless, the exact mechanisms explaining the beneficial effect of WBC on mood disorders remain unclear. The study aimed to assess the efficacy of repetitive short exposure to extremely low temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 57 publications
0
29
0
2
Order By: Relevance
“…In the second randomized and double-blind study from the same clinical site, conducted by Rymaszewska et al, the effectiveness of repeated short exposures to extremely low temperatures was assessed through the use of WBC on mood, quality of life, and biochemical parameters among outpatients with the diagnosis of depression who were treated pharmacologically [ 16 ]. The study involved 92 participants, aged 20–73 years, diagnosed with a depressive episode according to ICD-10.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the second randomized and double-blind study from the same clinical site, conducted by Rymaszewska et al, the effectiveness of repeated short exposures to extremely low temperatures was assessed through the use of WBC on mood, quality of life, and biochemical parameters among outpatients with the diagnosis of depression who were treated pharmacologically [ 16 ]. The study involved 92 participants, aged 20–73 years, diagnosed with a depressive episode according to ICD-10.…”
Section: Resultsmentioning
confidence: 99%
“…The criterion of recovery at the T4 visit was met by 66.7% in the study group and 57.14% in the reference group ( p = 0.55). Finally, the researchers concluded that WBC is an effective method supporting the pharmacological treatment of depression, and has a positive effect on the well-being and quality of life of people suffering from depression [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CCT is believed to induce the formation of new neuronal connections (neuroplasticity) and maintain the already existing pathways, while, WBC targets the neurodegenerative process by means of regulating the production of inflammatory mediators, such as cytokines IL-6 and IL-10 (55), nitric oxide (NO) (22). These mediators are released as a consequence of amyloidbeta deposition and the inflammatory response caused by the deposits.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic review revealed that WBC may exert beneficial effects on the lipid profile in terms of lowering the levels of total cholesterol, LDL, and triglycerides (21). Preliminary studies suggest that it may also be an effective method of improving cognitive functioning, especially memory processes (22). According to current knowledge, vascular malfunction, mitochondrial damage, oxidative stress and inflammatory response contribute to the development of cognitive deterioration, and WBC might be a response to these processes (20, [23][24][25][26].…”
Section: Whole-body Cryotherapymentioning
confidence: 99%